Uji Ketahanan Salinitas Beberapa Varietas Jagung (Zea mays L.) Dengan Menggunakan Agen Seleksi NaCl - Amirullah Dachlan; Nurlina Kasim; A Kurnia Sari (Biogenesis: Jurnal Ilmiah Biologi, 2013)
This study aims to determine the concentration of NaCl which can be used as maize resistance limit to salinity and to obtain varieties that are tolerant to salinity. This research was conducted in the form of an experiment with randomized design factorial using two factors in the group. As the first factor is the variety of Arjuna, Sukmaraga, Bhishma, Gumarang, Heroine Yellow, Pacakka, Anoman-1, and LAMURU. The second factor is the concentration of NaCl with 0 g L-1, 3 g L-1, 4 g L-1, and 5 g L-1. The results showed that the level of resistance of some maize varieties to salinity using NaCl produce varieties that have different resistance levels to high levels of salinity, there are varieties that can withstand the high NaCl concentration and some are only able to survive on a low NaCl concentration. The test results obtained sequentially showed varieties that are resistant to salinity is Pacakka. The concentration of 5 g L-1 NaCl can not be used as a concentration limit for the grouping of maize resistance to salinity.Keywords: Maize (Zea mays L.), NaCl, Salinity